Metode Bercerita Bagi Perkembangan Berbicara Pada Anak Usia Dini Di TK Bina Putra Mandiri Cimahi (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Storie telling tell to children is an activity that is considered good for early childhood speech development. Speaking is a delivery of ideas through words to others. In addition, speaking can convey how the child feels. The purpose of this study was conducted to see the effect of the storytelling method for the development of speech in children at Bina Putra Mandiri Cimahi Kindergarten. The indicators used in this study are answering greetings, reciting prayers, naming animals, naming parents and telling simple things. This research was conducted in two cycles of meetings. The results showed that the storytelling method can improve children's speaking ability and can increase children's self-confidence.